Studi Analisis Sifat Dielektrik Tanah dengan Variasi Porositas Pada Frekuensi Resonansi Rendah - Sehah, Sehah; Aziz, Abdullah Nur (Jurnal Fisika FLUX, 2009)
The equipment to measure dielectric properties of soil samples withlissajous method has been designed in Electronic and InstrumentationsLaboratory, Faculty of Science and Technique, Jenderal Soedirman University,Purwokerto. The fundamental parts of this equipment are signal generator,cathode ray oscilloscope (CRO) and parallel plate. Thus, the soil samples whichbe researched is placed in zone between parallel plate, as dielectric material. Ifsignal generator supply electric field into the parallel plate, hence response ofsamples to electric field is shown with voltages values on oscilloscope (CRO).Based on this voltages values, so that can be calculated a dielectric permittivity,dielectric loss and tangent loss of soil samples. The number of samples thatmeasured its dielectric properties are three samples, which contains of top soil,smooth sand of river, and sediments rocks. The measurement to dielectricproperties with variation of porosity is done to samples at low resonancefrequency of 600 kHz and 2,75 MHz. The results which obtained show that alinear relation between dielectric constant of soil samples to its porosity, but withempirical equations different for every samples.